2018
DOI: 10.32598/hdq.4.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Job Satisfaction of Prehospital and Hospital Emergency Nurses in Mashhad, Iran

Abstract: Background: Job satisfaction and its effective factors are important issue in productivity improvement. The main purpose of this study is to determine the job satisfaction of nurses in pre-hospital and hospital emergency rooms of Mashhad health system. Materials and Methods:The present study was descriptive-analytic with cross-sectional design carried out on nurses working in 168 pre-hospital emergency bases and 12 emergency departments of public hospitals of Mashhad affiliated to Mashhad University of Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In agreement with this study, in the study by Basaber et al [33], it was also found that there was a moderate level of job satisfaction among emergency medical staffs. However, in the above study, job satisfaction is closely related to gender and it is not in line with the findings of this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with this study, in the study by Basaber et al [33], it was also found that there was a moderate level of job satisfaction among emergency medical staffs. However, in the above study, job satisfaction is closely related to gender and it is not in line with the findings of this study.…”
Section: Discussionsupporting
confidence: 91%
“…In the study by Sonems et al [ 34 ], the overall level of job satisfaction of emergency physicians was rated as high, which is inconsistent with the results of this study. It should be noted that pre-hospital emergency has led to the creation of special conditions for this staffs due to special environmental conditions, time constraints, road traffic, the openness of the workspace, and the expectations of the companions [ 33 ] that it can be said that job satisfaction impacted by these factors, so we see the difference in the results of the two studies. Although the samples of this study are different from those in the Sonmez et al study.…”
Section: Discussionmentioning
confidence: 99%
“…The results of one study showed that the motivation of nurses in Iran is moderate-to-high [38], which is somewhat inconsistent with the results of the present study. The results of one study showed that the level of job satisfaction in pre-hospital EMS nurses is higher than the average [39], while in another study the level of job satisfaction in pre-hospital EMS personnel was low [40]. Although job satisfaction was not exactly considered in the present study, the participants have expressed their discomfort of being in EMS as one of the challenges, which it can somehow reveal the job dissatisfaction of these people.…”
Section: Discussionmentioning
confidence: 61%
“…The research results taking into account gender are not consistent both in terms of job satisfaction and burnout ( 28 ). The study conducted by Basabr et al showed a negative and significant relationship between gender and job satisfaction, but the comparison concerned men in pre-hospital emergency services and women in hospital settings ( 29 ). A study conducted by van der Ploeg et al ( 30 ) showed that factors such as lack of social support from colleagues and superiors, as well as poor communication, turned out to be significant predictors of low job satisfaction, post-traumatic stress disorder, symptoms of burnout and fatigue ( 31 ).…”
Section: Discussionmentioning
confidence: 99%